A total-evidence phylogenetic approach to understanding the evolution, depth transitions, and body-shape changes in the anglerfishes and allies (Acanthuriformes: Lophioidei) - Alex J. Maile; W. Leo Smith; Matthew P. Davis (PLoS ONE, 2025)
The anglerfishes and allies (Lophioidei) are a diverse group of fishes with over 400 carnivorous species that are renowned for their remarkable hunting behavior employing a modified first dorsal-fin spine to lure prey and adaptations such as “pseudo-walking,” bioluminescence, and parasitic sexual dimorphism. Gaining a comprehensive understanding of their evolutionary history has been challenging, as previous studies using DNA sequence data or morphological traits have provided either inconsistent or contradictory results. We present a new comprehensive phylogenetic framework for the evolution of the Lophioidei, combining ultraconserved elements (UCEs), mitochondrial DNA sequence data, and morphological characters. Our findings reveal a monophyletic Lophioidei, positioned as the sister group to the Tetraodontoidei within a broader acanthuriform radiation. Goosefishes (Lophioideo) emerge as the stem anglerfish lineage, forming a sister clade with frogfishes (Antennarioideo) + batfishes (Ogcocephaloideo) and coffinfishes (Chaunacoideo) + deep-sea anglerfishes (Ceratioideo). We expanded the Antennariidae to include all previous frogfish (antennarioid) families as subfamilies while proposing a new subfamily, Fowlerichthyinae, to produce a stable monophyletic taxonomy for the Antennarioideo. Further, we evaluated previously and newly proposed morphological characters to diagnose the Lophioidei and Lophioideo. Our investigations demonstrated that several traditional synapomorphies are no longer diagnostic for the Lophioidei. Based on our phylogeny, a geometric morphometric analysis revealed significant differences in body shape among lophioid infraorders, especially in frogfishes and deep-sea anglerfishes, indicating the importance of habitat transitions on body-shape evolution. This study, integrating genome-scale nuclear, mitochondrial, and morphological data, provides a total-evidence perspective on the evolutionary history of lophioids and sheds light on their specializations and body-shape changes as they transitioned across and within environments.